Does triple negative breast cancer subtype carry poorer prognosis as compared to non-triple negative breast cancer lesion - A study from a tertiary hospital - Srijan Basu,; Mintu Mohan Nandi,; Ranjit Kumar Haldar,; Amit Kumar Das, (Asian Journal of Medical Sciences, 2023)
Background: The breast cancer (BC), in spite of tremendous advances has continue to remain an enigma. The major change in understanding of BC has taken place after understanding of molecular biology. Aims and Objectives: The objectives are as follows:(1) To categorize the incidence of triple negative BC (TNBC) in hospital based data. (2) To study the prognostic outcomes of TNBC. Materials and Methods: The study was an observational prospective for the period of 18th months, from February 2014 to August 2015, where total 146 cases were selected. The data regarding age, sex, tumor size, stage, grade, nodal status, Nottingham prognostic index (NPI), morphology was noted. All patients underwent immunohistochemistry (IHC) study, maintaining higher quality assurance in the same IHC laboratory. Results: Our study revealed that out of 146 patients, 71 patients are TNBC. The mean age of presentation was 54.06 years in TNBC group. About 69.0% patients presented with Grade III tumor and 74.6% patient presented with NPI ≥5.4 among TNBC. However, 56% patients presented with NPI ≥5.4 among NON TNBC. Most of the morphological variant was IDC (95.8%), 85.9% patients presented with only lymph nodes metastasis among TNBC. Conclusion: The study is tremendously significant from Indian perspective. It proofs that TNBC had the point of diagnosis, seems to be more aggressive. It suggests that Indian BC is likely to be younger at presentation as compared to its Western counterpart.